High pressure Raman study and phase transitions of KIO3 non-linear optical single crystals - Shen, Z. X (2018)
Potassium iodate KIO3 single crystal samples have been studied under pressure up to 35 GPa at room temperature. Drastic spectral changes and phase transitions were observed. The first phase transition occurs at 5. 0 GPa characterised by major spectral changes in the Raman bands belonging to the v1, v2, and v4 modes. The other phase transitions were found at 8. 7, 15 and 22 GPa. The v1 modes soften with pressure up to 15 GPa The phase that is stable between 15-22 GPa has a higher symmetry than the phases in the lower pressures. The IO3 pyramidal ions may have lost their identity and changed to IO6 octahedra above 22 GPa, as indicated by the changes in the Raman bands of the v1 modes and the new bands in the spectral region between 500-600 cm-1.